2000
DOI: 10.1557/jmr.2000.0189
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Boron-doped Submicron Vapor-grown Carbon Fibers and Their Anode Performance

Abstract: Structural evolution of undoped and boron-doped submicron vapor-grown carbon fibers (S-VGCFs) was monitored as a function of heat-treatment temperature (HTT). Based on x-ray and Raman data, over the range of HTT from 1800 to 2600 °C, it was found that boron atoms act as catalysts to promote graphitization due to boron's higher diffusivity. For the range of HTT from 2600 to 2800 °C, the process of boron out-diffusion from the host material induces defects, such as tilt boundaries; this process would be related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 22 publications
(36 reference statements)
1
3
0
Order By: Relevance
“…As a result, previously diffused boron atoms in substitutional sites would, at high HTT (above 2500ЊC), diffuse out from the substitutional sites to form boron carbide, consistent with the synthesis temperature for boron carbide known to be at 2500ЊC. 16 These structural features with different morphologies found in borondoped MCMBs may degrade their electrical properties, because homogeneous morphology may be an important factor for producing high-performance anode materials.…”
Section: Characterization Of Boron-dopedsupporting
confidence: 59%
“…As a result, previously diffused boron atoms in substitutional sites would, at high HTT (above 2500ЊC), diffuse out from the substitutional sites to form boron carbide, consistent with the synthesis temperature for boron carbide known to be at 2500ЊC. 16 These structural features with different morphologies found in borondoped MCMBs may degrade their electrical properties, because homogeneous morphology may be an important factor for producing high-performance anode materials.…”
Section: Characterization Of Boron-dopedsupporting
confidence: 59%
“…It is well-known that the high-temperature boron doping technique was highly efficient to jump up the electrical conductivity of carbon materials including carbon nanotubes. 20,21 Main advantages of high-temperature thermal diffusion over an aerosol CVD are as follows: (1) Highly crystalline MWNTs can be obtained because boron atoms act as graphitization accelerators around 2000°C. 21 (2) The relative amount of the substitutional boron atoms with regard to other types of boron species are quite high.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that substitutionally introduced boron atoms allow multiwalled carbon nanotubes (MWNTs) to have a semimetallic character with a vanishing or narrow band gap. , Up to now, an aerosol CVD technique has been used to synthesize boron-doped MWNTs. However, TEM images of the aerosol CVD-grown MWNTs exhibited highly disordered and undulated fringes and sometimes cone-stacked structures. When considering the electrical conductivity of an individual MWNT, a nested MWNT with straight, long crystalline layers is highly desirable because the defects present in the tubes act as scattering centers in electron transport. It is well-known that the high-temperature boron doping technique was highly efficient to jump up the electrical conductivity of carbon materials including carbon nanotubes. , Main advantages of high-temperature thermal diffusion over an aerosol CVD are as follows: (1) Highly crystalline MWNTs can be obtained because boron atoms act as graphitization accelerators around 2000 °C . (2) The relative amount of the substitutional boron atoms with regard to other types of boron species are quite high.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, carbon nanomaterials have attracted considerable attention since the discovery of fullerene in 1985 [2]. Carbon nanotubes (CNTs) [3,4] and various types of carbon nanofibers (CNFs) [5] have also drawn increasing attraction.…”
Section: Introductionmentioning
confidence: 99%